Role of the Purinergic Receptor P2XR4 After Blunt Chest Trauma in Cigarette Smoke-Exposed Mice. Issue 2 (February 2017) - Hafner, Sebastian; Wagner, Katja; Weber, Sandra; Gröger, Michael; Wepler, Martin; McCook, Oscar; Scheuerle, Angelika; Stahl, Bettina; Huber-Lang, Markus; Jung, Birgit; Calzia, Enrico; Georgieff, Michael; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : ABSTRACT: Both acute and chronic lung injury are associated with up-regulation of the pulmonary expression of the purinergic receptors P2XR4 and P2XR7. Genetic deletion or blockade of P2XR7 attenuated pulmonary hyperinflammation, but simultaneous P2XR4 up-regulation compensated for P2XR7 deletion. Therefore, we tested the hypothesis whether genetic P2XR4 deletion would attenuate the pulmonary inflammatory response and thereby improve organ function after blunt chest trauma in mice with and without pretraumatic cigarette smoke (CS) exposure. After 3 weeks to 4 weeks of exposure to CS, anesthetized wildtype or P2XR4 −/− mice (n = 32) underwent a blast wave-induced blunt chest trauma followed by 4 h of lung-protective mechanical ventilation, fluid resuscitation, and noradrenaline support to maintain mean arterial pressure >55 mm Hg. Hemodynamics, lung mechanics, gas exchange, and acid-base status were measured together with blood and tissue cytokine and chemokine concentrations, heme oxygenase-1, B-cell lymphoma-extra large ( Bcl-xL), endogenous nuclear factor-κB inhibitor (IκBα) expression, nitrotyrosine formation, purinergic receptor expression, and histological scoring. Despite a significant increase in the histopathology score in both CS-exposed groups, neither CS exposure nor P2XR4 deletion had any significant effect on post-traumatic pulmonary function and inflammatory response. However, P2XR4 deletion was associated with attenuated impairment of glucose homeostasis and acid-base-status after CS exposure and chest trauma. In conclusion, genetic P2XR4 deletion failed to attenuate the acute post-traumatic pulmonary inflammatory response. The improved glucose homeostasis and acid-base-status after CS exposure in the P2XR4 −/− group was possibly due to less alveolar hypoxia-induced right ventricular remodeling resulting in preserved liver metabolic capacity.